The Impact of Customer Engagement on Loyalty Toward Halal Products: Mediating Role of Satisfaction - Mesra B; Elfitra Desy Surya; Muhammad Syahrin Asman (Society)
This research explored consumer involvement to increase customer loyalty to halal products. This study aims to test and analyze the influence of consumer engagement to increase customer loyalty to halal products through satisfaction. This research was carried out using a quantitative method, namely, research data in the form of numbers and statistical analysis. The population in this study is customers who shop for typical Medan souvenirs, which amounts to 200 customers. The study found that psychological, behavioral, and cognitive variables positively and significantly affected satisfaction. In contrast, emotions did not have a significant effect on satisfaction. Consumer involvement does not run effectively in increasing customer loyalty to halal products due to several conditions: limited knowledge and experience and consumer understanding of halal products reduce consumer motivation and desire to consume halal products. Consumer involvement does not run effectively in increasing customer loyalty to halal products due to several conditions: limited knowledge and experience and consumer understanding of halal products reduce consumer motivation and desire to consume halal products. Contribution in the field to provide input to industry players by Medan Typical to pay more attention to the halal logo on the products produced to increase customer satisfaction and loyalty.